Antibiotik sebagai Induktor Buah Tanpa Biji pada Anggur - Winarso Drajad Widodo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
Four kinds of antibiotics were examined, viz. streptomycin (SM) and gentamicin (GM) as bactericidal antibiotica and tetracycline (TC) and spectinomycin (SE) as bacteriostatical antibiotics. Kyoho an Pione (tetraploid hybris cultivars) were used as the plant materials. Among the four antibiotics, SM and SE were effective to induce seedlessness in Muscat of Alexandria (MOA) and less effective for Kyoho and Pione. The seedless induction effect of SM and SE seemed not to be affected by their mode of action. Using the four cultivars, Kyoho, Pione, MOA, and Neo Muscat (NM), either SM or SE most effective to induce seedlessness when applied 3 days before full bloom. The ineffectiveness of antibiotics for Kyoho and Pione was indicated by the higher percentage of empty-seeded berries in these cultivars compared to MOA and Nm. Since there was no normal seed in the antibiotic-treated berries, this phenomenon indicated that the outer parts of the tetraploid ovules were more resistant to antibiotic treatments than those of diploid ovules. Key word: Grape, Seedless, Antibiotics